STRUKTUR DAN CIRI KEBAHASAAN TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 12 SOLOK SELATAN - Tarida, Elga; Tamsin, Andria Catri; Zulfikarni, Zulfikarni (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTÂ  This study aims to (1) describe the structure of the report text observation of the work of class VII SMP Negeri 12 Solok Selatan (2) illustrates the linguistic characteristics of the observation report text by class VII SMP Negeri 12 Solok Selatan. The results of this study are as follows. First, in writing the report text of observations of Grade VII students of class VII SMP Negeri 12 Solok Selatan, they have used the three text structures of the observation report results. The structure of the report's observational text is a general definition, section description, and description of benefits. This is evident from the 20 observational report texts that have been analyzed throughout the observation report text of class VII SMP Negeri 12 Solok Selatan complete using general definitions, section descriptions, and benefits descriptions. Second, in writing the report text of observations generally in class VII SMP Negeri 12 Solok Selatan have used the four text structures of the observation report. The Fourth linguistic characteristics of the text of the observation report are repetition, pronoun, conjunction, and description sentences. This is evident from the 20 text reports on observations that have been analyzed, there are 16 text reports on observations that are complete using the linguistic characteristics of repetition, pronouns, conjunctions, and sentence definitions. Kata Kunci:Â Struktur Teks, Ciri Kebahasaan, dan Teks Laporan Hasil Observasi